A Study of Auditory Speech Processing Using Brainstem Evoked Responses Under the Effects of Stressors - Al Osman, Rida (Université d'Ottawa / University of Ottawa, 2016)
This work investigated the effects of various stressors on auditory speech processing using speech-evoked auditory brainstem response (ABR). This work was carried out in three distinct studies: (1) the effects of stimulus rate and noise on the speech-evoked ABR, (2) the effects of direct, early, and later-arriving speech reflections on the speech-evoked ABR, and (3) the effects of self-masking and overlap masking in a reverberant environment using speech-evoked ABR. Results from the first study indicate a complex interaction of fast stimulus rate and noise on the speech-evoked ABR. In particular, dissociation was found between electrophysiological responses to the envelope and the responses to the temporal fine structure or transient waves. The main finding from the second study is that direct sound and early reflections produce similar speech-evoked ABR, while the response to late reverberation shows different characteristics. Results from the third study indicate that severe reverberation significantly weakened the ABR when compared to anechoic or moderate reverberation, while moderate reverberation significantly enhanced the ABR when compared to anechoic speech. Overall, the new findings from this research shed light on the effects of stressors such as noise, increased stimulus rate, and reverberation. Up until now, these effects have mostly been studied perceptually. Our research demonstrates that these effects can be studied electrophysiologically using speech-evoked brainstem responses. This method of investigation permits the probing of particular stages of the auditory pathway and evaluating how neural activity in response to specific elements of speech, such as the fundamental frequency and formants, is affected by different stressors.
Keywords: Brainstem evoked responses; Effects of stressors; Noise; Reverberation; Fast stimulus rate